1999
DOI: 10.1029/1999wr900178
|View full text |Cite
|
Sign up to set email alerts
|

The entrapment and long‐term dissolution of tetrachloroethylene in fractional wettability porous media

Abstract: Abstract. Theoretical and modeling studies for the prediction of nonaqueous phase liquid (NAPL) entrapment and dissolution have largely assumed that the soil is preferentially water-wet. Many natural systems, however, have both water-and NAPL-wet solids as a result of spatial and temporal variations in fluid and soil properties. This condition is referred to as fractional wettability. This work presents long-term dissolution data for tetrachloroethylene (PCE) entrapped in porous media representing a range of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(31 citation statements)
references
References 41 publications
4
27
0
Order By: Relevance
“…Furthermore, the curvature and surface roughness of the grain particles may even further impede the flow within the film layer. In accordance with these observations, Bradford et al [89] experimentally showed that the interphase mass transfer in NAPL-wet media is much greater than the water-wet media providing further evidence that the flow configurations depicted in Fig. 3 can be useful in identifying which components of the interfacial areas contribute the most to interphase mass transfer ''MNtoIW'' can be visualized from Fig.…”
Section: Pore Scalesupporting
confidence: 55%
See 3 more Smart Citations
“…Furthermore, the curvature and surface roughness of the grain particles may even further impede the flow within the film layer. In accordance with these observations, Bradford et al [89] experimentally showed that the interphase mass transfer in NAPL-wet media is much greater than the water-wet media providing further evidence that the flow configurations depicted in Fig. 3 can be useful in identifying which components of the interfacial areas contribute the most to interphase mass transfer ''MNtoIW'' can be visualized from Fig.…”
Section: Pore Scalesupporting
confidence: 55%
“…Bradford et al [89] confirmed this phenomenon on fractional wettable media which is a mixture of water-wet and NAPL-wet media. The authors showed that in water-wet media residual NAPL exists as single or multi-pore blobs.…”
Section: Wettabilitymentioning
confidence: 72%
See 2 more Smart Citations
“…Calculated values of y&j and fofol* for organic components of the synthetic DNAPL mixture ( 16) (14). The initial organic saturation for the 0, 25, pore structure.…”
Section: Fractional Wettability Soilsmentioning
confidence: 99%